2019
DOI: 10.1097/ta.0000000000002285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of damage control laparotomy on major abdominal complications and lengths of stay: A propensity score matching and Bayesian analysis

Abstract: BACKGROUND In patients for whom surgical equipoise exists for damage control laparotomy (DCL) and definitive laparotomy (DEF), the effect of DCL and its associated resource utilization are unknown. We hypothesized that DEF would be associated with fewer abdominal complications and less resource utilization. METHODS In 2016, six US Level I trauma centers performed a yearlong, prospective, quality improvement project with the primary aim to safely decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…On the other hand, the reduced operative times were indeed associated with a significant shorter ICU and hospital stays, regardless of the presence of sepsis prior to surgery, the estimated TBSA affected and the ASA classification. The concept of reducing length of ICU and hospital stay by reducing operative times has not yet been described for NSTIs, but has been suggested for surgical procedures in trauma and general surgery [ 8 , 22 ]. Procter et al studied general surgical procedures and found that the odds ratio for ICU admission, adjusted for operative and patient risk variables, increased with 0.32 each half-hour of extra operative time and the hospital length of stay increased with 6% with each half hour extra operative time [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the reduced operative times were indeed associated with a significant shorter ICU and hospital stays, regardless of the presence of sepsis prior to surgery, the estimated TBSA affected and the ASA classification. The concept of reducing length of ICU and hospital stay by reducing operative times has not yet been described for NSTIs, but has been suggested for surgical procedures in trauma and general surgery [ 8 , 22 ]. Procter et al studied general surgical procedures and found that the odds ratio for ICU admission, adjusted for operative and patient risk variables, increased with 0.32 each half-hour of extra operative time and the hospital length of stay increased with 6% with each half hour extra operative time [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another propensity-matched cohort study, Harvin et al reported that use of DC instead of definitive laparotomy [for intra-abdominal packing (68%), second-look laparotomy (6%), hemodynamic instability (15%), to expedite postoperative care or intervention (8%), abdominal compartment syndrome prophylaxis (1%), contamination (1%), or other/unclear reasons (1%)] was associated with a significantly increased incidence of gastrointestinal (GI) ileus and bleeding, abdominal fascial dehiscence, superficial surgical site infection (SSI), and death [19]. Finally, in a follow-up study by Harvin et al in 2019, injured patients who underwent DC laparotomy across six American, level-1 trauma centers and were judged by majority faculty vote to have been candidates for definitive laparotomy were matched 1:1 with those who underwent definitive trauma laparotomy at these centers using propensity scores [42]. In this study, for those whom surgeons had equipoise Table 2 Highest rated candidate indications for use of damage control surgery in civilian trauma patients.…”
Section: Vascular Damage Control Interventionsmentioning
confidence: 99%
“…We previously hypothesized that variation in use of DC surgery among trauma centers may occur when surgeons are uncertain which operative profile is best across the large number of varying clinical situations encountered regarding use of DC or definitive laparotomy, definitive laparotomy was associated with a significantly higher probability of fewer hospital-free, ventilator-free, and ICU-free days, suggesting that use of definitive laparotomy in this setting may decrease hospital resource utilization [42]. However, the two groups demonstrated a similar probability of major abdominal complications [42]. [3].…”
Section: Published Appropriateness Indications For Use Of DC Surgery and Dc Interven-tions In Civilian Trauma Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 872 patients, there was no difference in the incidence of major abdominal complications, but definitive laparotomy was associated with fewer hospital, ICU, and ventilator days. [20] Further study has been done at the University of Texas-Houston aiming to decrease the number of DCLs performed. Audits and feedback after each case led to a decrease in DCL, from 39% in the control group (2011–2013), to 23% in the Q1 group (2013–2015), and subsequently to 17% after the study period.…”
mentioning
confidence: 99%